DAMPAK SOSIO-EKONOMIS DAN SOSIO-EKOLOGIS KONVERSI LAHAN - Astri Lestari, Astri; Hadi Dharmawan, Arya (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2011)
Conversion of agricultural land is one of the phenomena of change the agricultural land designated into non agricultural designated. The purposes of this study are 1) to know the types of land conversion at Desa Tugu Utara, 2) to know the social-economic impact of land conversion at Desa Tugu Utara, and 3) to know the social-ecological impact of land conversion at Desa Tugu Utara. This study uses a quantitative approach supported by the use of qualitative approach. The result of the study showed that the type of land conversion in the village (2000-2010) consists of three types of land conversion: 1) land conversion type by location (open/closed), 2) land conversion type by the speed of change of land utilization (fast/slow), and 3) land conversion type by the actors involved in the land conversion (local residents/non-local resident). In general, land conversion gives a negative impact on social-economics conditions of household in the region, either in the agricultural sector or in the non- agricultural sector and also brings a negative impact on social-ecological system because it causes many environmental degradation.